Caracterização e desenvolvimento de borrachas para almofadas de veículos militares sob lagartas - Valentim, Moisés Xavier Guimarães (2024)
Track pads are the part of tracked military vehicles that come into direct contact with the ground, therefore they are the most replaced item in combat vehicle maintenance due to friction wear. Field tests demonstrate that track pads supplied by different manufacturers show a wide variation in abrasion resistance and durability. In this context, the present study evaluated various rubber track pads supplied to the Brazilian Army with the aim of determining the characteristics required to improve their durability. Along with such characterization, this research evaluated SBR rubber with graphene addition as a possible alternative to improve pillow performance. For the characterization of rubber samples, chemical and thermal analysis as TGA, DSC, and FTIR, and mechanical tests such as tensile testing, hardness, and abrasion resistance. The results obtained showed that the rubbers had different compositions: the reference rubber is composed by characteristic groups of HNBR rubber, while the other rubbers from Manufacturers A, B, and C had a higher quantity of characteristic groups of styrene and butadiene polymers. The reference rubber showed better wear resistance, which was attributed to the presence of HNBR in its chemical composition. The higher the percentage of acrylonitrile, the greater the abrasion resistance of the material. Regarding SBR rubber with graphene addition, proportions of 0.1%, 0.3%, and 0.5% of graphene were studied. It was verified that the addition of graphene conferred an increase in wear resistance (0.5% was the best result), but it is still inferior to that of the reference rubber currently used in trackpads. For future work, it is recommended to evaluate the combination of SBR/NBR blends with graphene and silica, since the latter has already been proven to improve the abrasion resistance of the material.